KINETIC OF LIPID PRODUCTION BY Chlorella sp. IN PRODUCED WATER - Hajjar Rakhmadumila, Deby
Increased interest in renewable, carbon-neutral energy sources makes processing biodiesel from microalgae has become the objective for many researchers and companies. Some kind of wastewater including municipal, industrial and agricultural wastewaters have been identified as alternate growth mediums. Produced water is the largest byproduct of the oil and natural gas extraction process which constitutes of high concentration of pollutants, such as dissolved nitrogen, phosphorus, dissolved organic carbon, heavy metal and monocyclic aromatic compound like BTEX. The purpose of this study is to identify Chlorella sp. potential for producing lipid in artificial produced water. Variations made in this study consist of 0%, 25%, 50%, 75% and 100% volume of artificial produced water to the control Walne medium. Based on the results of the study, microalgae Chlorella sp. was able to live in all variations of produced water. This is indicated by maximum growth rate of 0.1997 day-1. Chlorella sp.was able to accumulate lipids in each variation of produced water with highest lipid content,lipid yield and lipid productivity was reached by the culture of 25% wastewater with a value of 23.33%, 0.2428, and 49.16 mg / L / day. The abundance of C16 and C18 fatty acids in Chlorella sp. lipids cultivated with 0%, 25%, 50%, 75% and 100% of wastewater were 61.29%, 87.12%, 77.49%, 77.49%, 99, 03% and 87, 89%. C16 and C18 fatty acids which dominated the lipids of Chlorella sp. in all culture variations indicated that the lipid of Chlorella sp. were suitable for producing high quality biodiesel. Based on qualitative calculations, biodiesel produced by Chlorella sp. in 100% wastewater has the best biodiesel characteristics, based on the parameters of cethane numbers, kinematic viscosity, oxidative stability, methyl ester content and high heating value.